2015
DOI: 10.1007/s00442-015-3382-7
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of prey-borne and predator-borne chemical cues for inducible antipredator responses in tadpoles

Abstract: Chemical cues that evoke anti-predator developmental changes have received considerable attention, but it is not known to what extent prey use information from the smell of predators and from cues released through digestion. We conducted an experiment to determine the importance of various types of cues for the adjustment of anti-predator defences. We exposed tadpoles (common frog, Rana temporaria) to water originating from predators (caged dragonfly larvae, Aeshna cyanea) that were fed different types and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 66 publications
(143 reference statements)
4
69
0
2
Order By: Relevance
“…Moreover, tadpoles are able to differentiate between predation cues from feeding on conspecifics or heterospecifics (Hettyey et al, 2015). ), and adult male smooth newts (Lissotriton vulgaris) from private ponds in Austria, and acquired juvenile threespined sticklebacks (Gasterosteus aculeatus) from a breeder.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, tadpoles are able to differentiate between predation cues from feeding on conspecifics or heterospecifics (Hettyey et al, 2015). ), and adult male smooth newts (Lissotriton vulgaris) from private ponds in Austria, and acquired juvenile threespined sticklebacks (Gasterosteus aculeatus) from a breeder.…”
Section: Methodsmentioning
confidence: 99%
“…The most likely reason may be related to the tadpoles' ability to recognize their predators. Some studies have shown that the tadpoles of many amphibian species can respond to the presence of chemical cues from local predators by reducing their activity levels or changing their space use as an adaptive anti-predator strategy (Ferrari et al 2016;Hettyey et al 2015). But there are actually several studies that show this is not the case and that native species do respond to non-native species.…”
Section: Discussionmentioning
confidence: 75%
“…Tadpole movement rates-thought to be ß1 m per day (Freidenburg 2003)-imply that individuals might contact multiple risk environments over the course of development. Many studies show that water-borne chemicals are the primary signal of predation risk for aquatic amphibian larvae (Petranka et al 1987;Stauffer and Semlitsch 1993;Hettyey et al 2015). Turner and Montgomery (2003) pointed out that moving prey should perceive spatially uneven degrees of risk if the average area occupied by a predator individual is greater than the area influenced by risk signals emanating from the predator.…”
Section: For Plasticitymentioning
confidence: 99%
“…Many studies show that water-borne chemicals are the primary signal of predation risk for aquatic amphibian larvae (Petranka et al 1987;Stauffer and Semlitsch 1993;Hettyey et al 2015). For example, the landscape of fear will be more structured if predators are clumped or if risk cues are produced primarily during infrequent interactions between predator and prey; both of these are true in my study system (Hettyey et al, 2010(Hettyey et al, , 2015Shaffery and Relyea 2016). The movement velocity of Aeshna dragonflies is ß1 m/h at night and much less during the day (Van Buskirk 1992), and invertebrate predator density ranges from zero to > 50/m 2 ( Fig.…”
Section: For Plasticitymentioning
confidence: 99%